The Visible Cosmos of Dialogues. Some Historical and Philosophical Remarks about Plato in the Late Antique Schools - Motta, Anna (Revista Archai, 2014)
Between the 5th and the 6th centuries A. D., the Neoplatonic school of Alexandria, where the philosophical didactic follows a specific cursus studiorum, is opened also to the Christian students. Despite some divergences of religious (but also of economical and of political) natures, and after some violent events which occur in the Egyptian city, the Alexandrian school is linked to its contemporary Neoplatonic school in Athens. And indeed the Prolegomena to Platonic Philosophy, i.e. the introductory lectures discussed by an Anonymous professor in order to present the characteristic of Platonic philosophy, show that the method of teaching Plato is still the same. According to the Neoplatonic exegetical tradition, the text emphasizes that the dialogical artefact fashioned as a cosmos by Plato is a paideutic instrument with a purpose to look away from the sensible and to guide towards the intelligible. Plato, through dialogues, eikones of the invisible, does not create illusions, but contributes to the practice of ‘assimilation’ by filling the writings with greater contents. KEY-WORDS: Plato, Prolegomena, analogy, visible cosmos, invisible cosmos.